Neutrophil-Specific Knockdown of β2 Integrins Impairs Antifungal Effector Functions and Aggravates the Course of Invasive Pulmonal Aspergillosis - Haist, Maximilian; Ries, Frederic; Gunzer, Matthias; Bednarczyk, Monika; Siegel, Ekkehard; Kuske, Michael; Grabbe, Stephan; Radsak, Markus; Bros, Matthias; Teschner, Daniel (Frontiers in Immunology, 2022)
β2-integrins are heterodimeric surface receptors that are expressed specifically by leukocytes and consist of a variable α (CD11a-d) and a common β-subunit (CD18). Functional impairment of CD18, which causes leukocyte adhesion deficiency type-1 results in an immunocompromised state characterized by severe infections, such as invasive pulmonary aspergillosis (IPA). The underlying immune defects have largely been attributed to an impaired migratory and phagocytic activity of polymorphonuclear granulocytes (PMN). However, the exact contribution of β2-integrins for PMN functions in-vivo has not been elucidated yet, since the mouse models available so far display a constitutive CD18 knockout (CD18-/- or CD18hypo). To determine the PMN-specific role of β2-integrins for innate effector functions and pathogen control, we generated a mouse line with a Ly6G-specific knockdown of the common β-subunit (CD18Ly6G cKO). We characterized CD18Ly6G cKO mice in-vitro to confirm the PMN-specific knockdown of β2-integrins. Next, we investigated the clinical course of IPA in A. fumigatus infected CD18Ly6G cKO mice with regard to the fungal burden, pulmonary inflammation and PMN response towards A. fumigatus. Our results revealed that the β2-integrin knockdown was restricted to PMN and that CD18Ly6G cKO mice showed an aggravated course of IPA. In accordance, we observed a higher fungal burden and lower levels of proinflammatory innate cytokines, such as TNF-α, in lungs of IPA-infected CD18Ly6G cKO mice. Bronchoalveolar lavage revealed higher levels of CXCL1, a stronger PMN-infiltration, but concomitantly elevated apoptosis of PMN in lungs of CD18Ly6G cKO mice. Ex-vivo analysis further unveiled a strong impairment of PMN effector function, as reflected by an attenuated phagocytic activity, and a diminished generation of reactive oxygen species (ROS) and neutrophil-extracellular traps (NET) in CD18-deficient PMN. Overall, our study demonstrates that β2-integrins are required specifically for PMN effector functions and contribute to the clearance of A. fumigatus by infiltrating PMN, and the establishment of an inflammatory microenvironment in infected lungs.